1986
DOI: 10.1111/j.1600-0528.1986.tb01063.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral hygiene and toothbrushing habits of 12‐year‐old children in Hong Kong

Abstract: Randomly selected groups of 486 Southern Chinese and 129 non-Chinese 12-yr-old Hong Kong children were examined for calculus and oral debris. The non-Chinese children had less plaque and calculus than the Chinese children (P less than 0.001). The girls had lower plaque scores than the boys in both ethnic groups. The higher frequency of toothbrushing by the girls possibly reflects their greater awareness of personal appearance. There is a need to increase the standard of oral hygiene and the level of dental awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Similarly, King et al . (4) found that girls in Hong Kong children brushed their teeth frequently compared with boys. In Kenya, 9.2–12.4% of the peri‐urban and urban children knew what causes dental caries.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, King et al . (4) found that girls in Hong Kong children brushed their teeth frequently compared with boys. In Kenya, 9.2–12.4% of the peri‐urban and urban children knew what causes dental caries.…”
Section: Introductionmentioning
confidence: 99%